2014
DOI: 10.1016/j.actatropica.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Epizootiological survey of small mammals as Leptospira spp. reservoirs in Eastern Croatia

Abstract: In this survey we investigated a population of small mammals in Eastern Croatia in order to determine Leptospira carriage rates and identify circulating serovars. Out of 67 trapped animals, 20 (29.9%) isolates were obtained. Identification of isolates using microscopic agglutination test, pulsed field gel electrophoresis and multi locus sequence typing revealed that 10 (50.0%) isolates belong to serogroup Pomona, serovar Mozdok, 6 (30.0%) isolates to serogroup Australis, serovar Jalna, 2 (10.0%) isolates to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
5
19
1
Order By: Relevance
“…have previously been implicated as reservoirs of Leptospira in Croatia. 32,33 Consistent with this earlier work, we found that 49 of 52 Leptospira-positive rodents represented Apodemus spp. Bacterial isolation from kidney tissue was successful in 40 PCR-positive rodents, and speciation assays indicated that 22 were L. interrogans, 16 L. kirschneri, and two Leptospira borgpetersenii.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…have previously been implicated as reservoirs of Leptospira in Croatia. 32,33 Consistent with this earlier work, we found that 49 of 52 Leptospira-positive rodents represented Apodemus spp. Bacterial isolation from kidney tissue was successful in 40 PCR-positive rodents, and speciation assays indicated that 22 were L. interrogans, 16 L. kirschneri, and two Leptospira borgpetersenii.…”
Section: Resultssupporting
confidence: 81%
“…41 Leptospira interrogans, L. kirschneri, and L. borgpetersenii were identified as the Leptospira species in our study, similar to previous reports from Croatian rodents. 32,33 Hantavirus and Leptospira also represented the most frequent coinfections. We previously showed coinfections with both agents in humans 10 and rodents 41,42 highlighting the potential risk for simultaneous transmission of these pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…ST (7LBoonsilp) 24 isolates were found associated with hedgehog and mouse (in Czech Republic) and human (in Germany) hosts (Boonsilp et al, ). These ST (7LBoonsilp) 24 isolates were also suspected of causing the death of beavers in south‐west Germany (Woll, Karnath, Pfeffer, & Allgower, ) and were among the most common isolates collected from small mammals in Eastern Croatia (Stritof Majetic et al, ). The hedgehog ( Erinaceus europaeus ) has been recognized for many years as the maintenance host for Bratislava (Sebek & Rosicky, ), but in the last decades, an increasing infection of Bratislava serovar has been observed in several free‐living and domestic species, namely in Europe (Arent, Gilmore, Brem, & Ellis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Croatia showed that 7.0% to 29.9% of small rodents carried Leptospira (Majetić et al 2014). In the Czech Republic, serological studies of 4634 samples from wild mammals found 12% positive, and of these, 99% had antibodies against serovars belonging to Grippotyphosa serogroup.…”
Section: Discussionmentioning
confidence: 99%